2015
DOI: 10.1101/014100
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrating crop growth models with whole genome prediction through approximate Bayesian computation

Abstract: Genomic selection, enabled by whole genome prediction (WGP) methods, is revolutionizing plant breeding. Existing WGP methods have been shown to deliver accurate predictions in the most common settings, such as prediction of across environment performance for traits with additive gene effects. However, prediction of traits with non-additive gene effects and prediction of genotype by environment interaction (G×E), continues to be challenging. Previous attempts to increase prediction accuracy for these particular… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
92
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(94 citation statements)
references
References 90 publications
(93 reference statements)
1
92
0
1
Order By: Relevance
“…using the model as an integrator that characterizes the growth environment), and second to extend the phenotyping per se at the level of the plot or plant, sometimes described as model-assisted phenotyping (Luquet et al, 2006;Rebolledo et al, 2015). A newly sought outcome from applications of CGMs is to combine their outputs of development and growth variables with knowledge from genomics and understanding of genetic architecture in order to predict the trait combinations, and eventually the allele combinations, that provide improved solutions in breeding (Technow et al, 2015).…”
Section: Crop and Plant Modelingmentioning
confidence: 99%
“…using the model as an integrator that characterizes the growth environment), and second to extend the phenotyping per se at the level of the plot or plant, sometimes described as model-assisted phenotyping (Luquet et al, 2006;Rebolledo et al, 2015). A newly sought outcome from applications of CGMs is to combine their outputs of development and growth variables with knowledge from genomics and understanding of genetic architecture in order to predict the trait combinations, and eventually the allele combinations, that provide improved solutions in breeding (Technow et al, 2015).…”
Section: Crop and Plant Modelingmentioning
confidence: 99%
“…Alleviating the phenotyping bottleneck for agriculturally important plants will help the world meet the increasing food and energy demands of the growing global population (Somerville et al, 2010;Alexandratos and Bruinsma, 2012;Cobb et al, 2013). Approaches to alleviate the plant phenotyping bottleneck fall into two broad categories: approaches that increase the number of individuals that can be grown and evaluated (Fahlgren et al, 2015b) and approaches that predict performance in silico to prioritize individuals to grow and evaluate (Hammer et al, 2010;Technow et al, 2015). Both of these approaches will be instrumental for increasing the rate of crop improvement, and both approaches are facilitated by advances in image-based phenotyping; multiple plant measurements can be acquired rapidly from images, and data from image-based phenotyping approaches also can inform performance prediction (Spalding and Miller, 2013;Pound et al, 2014).…”
mentioning
confidence: 99%
“…Recently, efforts are being made to directly incorporate CGMs into the estimation of whole genome marker effects in GP using an Approximate Bayesian Computation (ABC) method (Technow et al, 2015). Technow et al, (2015) demonstrated the use of ABC as a mechanism for incorporating substantial biological knowledge embodied in the CGMs into a GP approach and showed that their proposed approach can be considerably more accurate than a benchmark GP method in predicting performance in environments represented in the estimation set as well as in previously unobserved environments for traits determined by non-additive gene effects.…”
Section: Discussionmentioning
confidence: 99%
“…Technow et al, (2015) demonstrated the use of ABC as a mechanism for incorporating substantial biological knowledge embodied in the CGMs into a GP approach and showed that their proposed approach can be considerably more accurate than a benchmark GP method in predicting performance in environments represented in the estimation set as well as in previously unobserved environments for traits determined by non-additive gene effects. A key difference in our approach to that of Technow et al, (2015) is the way in which component traits are introduced. We assume that all the components are observable / measurable for all the genotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation